14‐3‐3 protein mediates plant seed oil biosynthesis through interaction with AtWRI1. (30th August 2016) - Ma, Wei; Kong, Que; Mantyla, Jenny J.; Yang, Yang; Ohlrogge, John B.; Benning, Christoph
Summary: Plant 14‐3‐3 proteins are phosphopeptide‐binding proteins, belonging to a large family of proteins involved in numerous physiological processes including primary metabolism, although knowledge about the function of 14‐3‐3s in plant lipid metabolism is sparse. WRINKLED1 (WRI1) is a key transcription factor that governs plant oil biosynthesis. At present, AtWRI1‐interacting partners remain largely unknown. Here, we show that 14‐3‐3 proteins are able to interact with AtWRI1, both in yeast and plant cells. Transient co‐expression of 14‐3‐3‐ and AtWRI1‐encoding cDNAs led to increased oil biosynthesis in Nicotiana benthamiana leaves. Stable transgenic plants overproducing a 14‐3‐3 protein also displayed increased seed oil content. Co‐production of a 14‐3‐3 protein with AtWRI1 enhanced the transcriptional activity of AtWRI1. The 14‐3‐3 protein was found to increase the stability of AtWRI1. A possible 14‐3‐3 binding motif was identified in one of the two AP2 domains of AtWRI1, which was also found to be critical for the interaction of AtWRI1 with an E3 ligase linker protein. Thus, we hypothesize a regulatory mechanism by which the binding of 14‐3‐3 to AtWRI1 interferes with the interaction of AtWRI1 and the E3 ligase, thereby protecting AtWRI1 from degradation. Taken together, our studies identified AtWRI1 as a client of 14‐3‐3 proteins and provide insights into a role of 14‐3‐3 in mediating plant oil biosynthesis. Significance Statement: WRINKLED 1 (WRI1), is a key transcription factor governing oil biosynthesis, but how its activity is modulated is unclear. Here we show that a 14‐3‐3 phosphopeptide‐binding protein affects turnover and hence activity of WRI1. We hypothesize a regulatory mechanism where the binding of a 14‐3‐3 to WRI1 interferes with binding of an E3 ligase to WRI1, thereby protecting WRI1 from degradation. Transgenic plants overproducing a 14‐3‐3 displayed increased seed oil content. Thus this protein‐protein interaction provides a tool set for enhancing oil content in plants.